Hubungan Pendidikan dan Level Pk Dengan Ketepatan Perawat dalam Melakukan Tindakan Resusitasi Jantung Paru (RJP) di Ruangan ICU dan IGD RS Prikasih Tahun 2024 - Ratu Memei Dwi Prianti; Weslei Daeli; Arif Hidayatullah (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Cardiopulmonary Resuscitation (CPR) or CPR is help for patients experiencing a heart attack where basic living rock is needed by applying pressure to the chest. Nurses have an important role in implementing cardiopulmonary resuscitation (CPR), especially in the emergency room. Skills in carrying out actions can have a direct impact on patient safety. Steps can be taken to improve the overall quality of medical treatment by increasing the education, knowledge and skills of attached nurses. The aim of this research is to find out the relationship between education and PK level with the accuracy of nurses in carrying out cardiopulmonary resuscitation measures in the ICU and emergency rooms at Prikasih Hospital in 2024. The research method that will be used is an analytical research design with a correlational design with a cross-sectional approach, a population of 40 technical respondents total sample and sample size of 40 respondents. Using the non-parametric Rank Spearman Rho test. The results show a relationship between education and the accuracy of nurses in carrying out cardiopulmonary resuscitation (CPR) in the ICU and ER with a P-Value of 0.026 < 0.05. And there is a relationship between the PK level and the accuracy of nurses in carrying out cardiopulmonary resuscitation (CPR) in the ICU and ER with a P-Value of 0.002 < 0.05. The conclusion is that education and level PK are very important in carrying out actions, because a person's knowledge can be seen from the abilities or skills they have, therefore education and level PK greatly influence the accuracy of cardiac resuscitation actions.